337 Pulmonary Agenesis, MICROPHTHALMIA, DIAPHRAGMATIC DEFECT ASSOCIATION. (1st January 2006) - Bird, L. M.; Shayan, K.; Jones, M. C.
Abstract : A healthy 25-year-old woman was found at 22 weeks' gestation to have a fetus with diaphragmatic hernia. In addition, the orbits were closely set and the ocular diameter of 7-8 mm was < 5th centile, indicating microphthalmia. MRI of the fetus confirmed these findings and did not reveal any additional abnormalities. An apparently normal right lung and right hemidiaphragm were visible on MRI. Amniocentesis revealed a normal male karyotype and FISH for 12p revealed no aneuploidy in 100 interphase cells. The baby was delivered at term weighing 3.1 kg, measuring 52 cm, with a head circumference of 34.5 cm. Apgar scores were 2, 5, and 5 at 1, 5, and 10 minutes. There was bilateral microphthalmia with palpebral fissures measuring 1.2 cm; remnants of globes but no visible sclera, iris, or pupil; and normal-appearing eyelids and lashes. The remainder of the external examination was normal. At the time of surgical repair, the left diaphragm was nearly absent except for a rim of tissue at the lateral margin. The right diaphragm consisted of a thin membrane devoid of muscle in the central area into which the right liver had eventrated. The left lung was a small nubbin of tissue and the right lung appeared normal. The left diaphragm was repaired with a Goretex patch and the right diaphragm was plicated. Postoperatively, the baby was very unstable and had poor oxygenation, and he died at 2 days of age. Microphthalmia and diaphragmatic defects are seen together in a variety of syndromes, including Fryns, Goltz, Pallister-Killian, WAGR, Goldenhar, de Lange, Fraser, and hydrolethalus syndromes. These can be ruled out due to the absence of other abnormalities in this baby. There is also an apparently nonrandom association of pulmonary agenesis, microphthalmia/anophthalmia, and diaphragmatic defects (hernia or eventration) that has been called PMD association. The pulmonary agenesis is felt to be a primary abnormality (rather than secondary to the diaphragmatic defect) because of the absence of pulmonary vessels. The PMD association has been reported in four infants previously; the similarities and differences with the present case will be discussed.